PENGARUH TOTAL QUALITY MANAGEMENT DALAM MENINGKATKAN PRODUKTIVITAS DAN KUALITAS PEKERJA PADA GALANGAN KAPAL KAYU PINISI, TANAH BERU, BULUKUMBA - Risal Risal (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2022)
The purpose of this study was to determine the effect of Total Quality Management (TQM) using 4 variables namely age, length of work, number of family dependents, and the number of workers working around in increasing the productivity and quality of workers in the pinisi wooden shipyard industry, Tanah Beru Village, Bonto Bahari District, Bulukumba Regency. The sample studied was 42 workers obtained based on the accidental method and the results showed that the age variable did not have a positive influence in increasing the productivity and quality of workers, while the other 3 variables, namely the variable number of family dependents, the variable length of work and the variable number of workers working around had a positive influence in increasing the productivity and quality of workers in the wooden pinisi shipyard industry, Tanah Beru Village, Bonto Bahari District, Bulukumba Regency.